Entrepreneurial education during pandemics: challenges and recommendations / Noorziah Mohd Salleh and Cristina Andin - Mohd Salleh, Noorziah; Andin, Cristina (Universiti Teknologi MARA, Cawangan Melaka, 2017)
In this article, an investigation of the challenges encountered by Higher Learning Institution students undertaking entrepreneurship course within the context of the COVID-19 pandemic is presented. In this study, seventy-nine students participated in this study for one semester for the Fundamentals of Entrepreneurship course, which employed a qualitative approach. A total of fifteen groups of students participated in the study. The data are derived from an analysis of the final project reports of the students, which contain a section dedicated to reflection on the challenges encountered during the project. Based on the results, there were two main challenges associated with the COVID-19 pandemic, namely, the Movement Control Order (MCO), which created problems with material supply, increased material costs, and loss of customers. Additionally, pandemics create logistical challenges. Meanwhile, the other four challenges are less tied to the pandemic, such as student factors such as commitment, time management, and skills. Students are also confronted with resource constraints such as a lack of business capital and a limited access to the Internet, as well as challenges related to product management and customer competition. It is anticipated that the results of this study will provide recommendations for improving entrepreneurship education programs among IHL students in the future